Involvement of Recipient Transplant Coordinators in Transplant Outpatient Clinics in Japan: Current Status and Transplant Physician's Thoughts on Follow-Up Clinics. (March 2017) - Hagiwara, Kuniko; Seto, Natsuko; Shimizu, Yasuko; Takahara, Shiro
Context: Transplant recipients require long-term immunosuppressive therapy, so continued medical follow-up is necessary for long-term survival. Objective: To investigate the current role of recipient transplant coordinators (RTCs) in the outpatient care of organ transplant recipients in Japan. Methods: We sent a questionnaire survey to doctors in transplant facilities affiliated with the Japan Society for Transplantation probing attitudes on the role of RTCs in outpatient clinics. The questionnaire assessed responses using an ordinal scale of 5 ranks. Results: In total, 139 responses were obtained from 233 transplant facilities. Respondents were divided into 2 groups, doctors currently working with RTCs (group A) and doctors not currently working with RTCs (group B). Differences in response rates between groups were analyzed using the Mann-Whitney U test. The overall attendance rate of RTCs in outpatient clinics was only 45%. Of all items on transplant outpatient clinics, group A exhibited a significantly higher response rate of "strongly agree" for "The involvement of an RTC in outpatient work can be expected to help prevent complications in transplant patients" ( P < .01) and "The involvement of an RTC in outpatient work can be expected to help prevent or reduce drug-related side effects in transplant patients" ( P < .01). Those with the highest rate of "strongly agree" were "It is necessary for RTCs to provide outpatient follow-up for transplant patients alongside doctors" (82.1% vs 67.3%, P < .07). Conclusion: We suggest that Japanese RTCs must participate more frequently in posttransplant outpatient care.